Acetylcholinesterase histochemistry: A very useful technique in the diagnosis of Hirschsprung’s disease - Tripathi, Brijesh K; Ghosh, Amrita; Pandey, Vaibhav; Gangopadhyay, Ajay N; Chawdhary, Sarita; Sharma, Shiv P (Journal of Neonatal Surgery, 2022)
Hirschsprung’s disease (HD) is a common congenital paediatric disorder. The gold standard for its diagnosis is the demonstration of the absence of ganglion cells on H&E stained sections from a spastic segment of the bowel, still at times; conclusive diagnosis of HD is difficult. This study was done to assess the accuracy of rapid Hematoxylin & Eosin (H&E) staining and AChE histochemistry in combination for the diagnosis of HD, especially in frozen section specimens. Samples from 36 clinically suspected HD cases were evaluated for the presence or absence of ganglion cells on H&E staining on both fresh-frozen and paraffin-embedded sections, whereas AChE staining was done on frozen sections only. Of the 36 cases of frozen section specimens from the spastic region of the colon, GCs were absent in 28 cases on H&E staining while positive staining patterns on AChE histochemistry were observed in 29 cases. Formalin-fixed paraffin-embedded sections showed the absence of GC on H&E staining in 28 cases. The sensitivity and specificity of frozen sections with rapid H&E were 77.78% and 81.82% while the sensitivity and specificity of AChE histochemistry were 80.56% and 81.82% respectively in the diagnosis of HD. Application of AChE histochemistry as an ancillary technique on frozen sections specimens of HD in combination with rapid H&E staining is very useful for definitive diagnosis of HD.